Seabird in the forest : the mystery of the marbled murrelet - Dunning, Joan, 1948- (Honesdale, Pa. : Boyds Mills Press, 2011)
Illustrations and text show how the marbled murrelet, a sea bird, make their nests and raise their chicks inland, hundreds of feet above ground, before they fly back and forth over the Pacific Ocean.
Includes bibliographical references.
Kirkus Review
Publisher's Weekly
Kirkus Review, March 2011
Publisher's Weekly, April 2011
4.1
Keywords: Birds -- Nests -- Juvenile literature; Birds -- California -- Juvenile literature; Marbled murrelet -- Juvenile literature; Sea birds -- Juvenile literature; Birds -- Nests; Birds -- California; Marbled murrelet; Sea birds; Birds -- Nests; Birds -- California; Marbled murrelets; Sea birds